Development of Learning Materials on Classification of Living Things Topic Based on Science Literacy and Local Wisdom - sri maida hartati (Indonesian Journal of Science Education and Applied Science, 2023)
The purpose of this study was to gacor5000 analyze the validity and consistency of the assessment of teaching materials for classification of living things based on scientific literacy and local wisdom.. This research model uses a 4-D development model, with the stages: (1) Define, (2) Design, (3) Develop, and (4) Disseminate. This research is only up to the stage of developing on expert validation. At the expert validation stage, teaching materials were validated by 4 validators. The results of the validity show that the teaching materials developed are very valid with a validity value of 88.77. The consistency of the assessment of teaching materials is categorized as quite reliable with a percentage value of 63%. In the future, further research will be carried out for these teaching materials, such as the trial phase of the development and distribution of teaching materials.